Cognitive and behavioral changes in rats under conditions of experimental ischemic stroke and their correction with mesenchymal stem cells and resveratrol - Khomut, Yu.; Savytskyi, I.; Ostapets, M. (Journal of Education, Health and Sport, 2024)
The article presents the results of studying cognitive and behavioral impairments in rats under conditions of experimental acute cerebrovascular accident and of evaluating the effectiveness of its correction with mesenchymal stem cells and resveratrol. On the first day after modeling acute cerebrovascular accident, a pronounced neurological deficit was observed, accompanied by an increase in McGraw Stroke Index values (p<0.05) and a significant reduction in locomotor and exploratory activity. A marked deterioration in cognitive functions was recorded, manifested by an increase in the diving latency in the extrapolation release test (p<0.05). On day 14, a partial restoration of functions was observed; however, the impairments remained statistically significant. The administration of mesenchymal stem cells contributed to a moderate improvement in behavioral parameters, whereas combined therapy provided a more pronounced effect, which was reflected by an increase in the number of crossed squares (p<0.05), an increase in the number of explored holes (p<0.05), and a reduction in diving latency (p<0.05) compared to untreated animals.